Fossil marine vertebrates of Cerro Los Quesos: Distribution of cetaceans, seals, crocodiles, seabirds, sharks, and bony fish in a late Miocene locality of the Pisco Basin, Peru. Issue 5 (19th October 2016) - Bianucci, Giovanni; Di Celma, Claudio; Collareta, Alberto; Landini, Walter; Post, Klaas; Tinelli, Chiara; de Muizon, Christian; Bosio, Giulia; Gariboldi, Karen; Gioncada, Anna; Malinverno, Elisa; Cantalamessa, Gino; et al.
ABSTRACT: One-hundred and ninety-two fossil marine vertebrate specimens, preserved as bone elements cropping out at Cerro Los Quesos (Pisco Basin, Peru), are identified and reported on a 1:4, 000 scale geological map and in the corresponding stratigraphic section. All the fossils originate from the Pisco Formation, which is dated in this area to the late Miocene (from 7.55 Ma to ≥6.71 Ma, based on 40 Ar/ 39 Ar analyses of three volcanic ash layers along the section). Specimens are particularly concentrated near the top of the two main hills, where the geologically youngest portion of the examined section crops out. The impressive fossil assemblage includes cetaceans (91.6%), represented by mysticetes (balaenopteroids and cetotheriids) and odontocetes (phocoenids, physeteroids, and ziphiids, including the holotype of Nazcacetus urbinai ). Seals, a crocodile, a seabird, bony fish, and sharks are also reported. Isolated large teeth of Carcharocles and Cosmopolitodus are common and, in several instances, associated to mysticete skeletons. Together with a similar work recently published for the other late Miocene locality of Cerro Colorado, this work represents a case study for the detailed inventory of the extraordinary paleontological heritage of the Pisco Basin. As such, it constitutes the basis for future taphonomic, paleoecological, and systematic studies, as well as for a much-needed conservation effort.